Imaging of metabolic bone disease - Mattera, Maria; Reginelli, Alfonso; Bartollino, Silvia; Russo, Claudio; Barile, Antonio; Albano, Domenico; Mauri, Giovanni; Messina, Carmelo; Cappabianca, Salvatore; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2018)
Osteoporosis is the most important metabolic bone disease, with a wide distribution among the elderly. It is characterized by low bone mass and micro architectural deterioration of bone tissue, leading to enhanced bone fragility and a consequent increase in fracture risk. Identify bone weakening with an appropriate and accurate use of diagnostic imaging is of critical importance in the diagnosis and follow-up of osteoporotic patients. The aim of this review is to evaluate the detection rates of the different imaging modalities in the evaluation of bone strength, in the assessment of fracture risk and in the management of fragility fractures.